Histoires et pratiques dissonantes dans un ghetto en devenir. Anthropologie contemporaine du cas de Venise - Antonella Di Trani (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The article proposes a new reading of the word ghetto with regard to the dense historical past of the case of Venice, a former enclave whose renewal is underway. While reviewing the semantic trajectory of the word ghetto and its use in different contexts, this contribution aims to show how the inhabitants, Venetian Jews, and young missionaries or newcomers, appropriate the local history of the ghetto in order to reaffirm their belonging to this "historical place", perceived differently by each in terms of the contemporary ghetto’s issues and transformations. Actors initiate narratives and reactivate competing sequences of history depending on their involvement in the ghetto and the meanings that they attach to it. Who owns the ghetto and its history? This question leads to dissonant uses of the past and conflicts of visibility and representation within the public space of an emerging ghetto.